The coordination of care for tuberculosis control - Assis, Elisangela Gisele de; Beraldo, Aline Ale; Monroe, Aline Aparecida; Scatena, Lúcia Marina; Cardozo-Gonzales, Roxana Isabel; Palha, Pedro Fredemir; Protti, Simone Terezinha; Villa, Tereza Cristina Scatena (Revista da Escola de Enfermagem da USP, 2012)
This descriptive epidemiological study analyzed the coordination of tuberculosis (TB) patient care in primary healthcare services according to 23 patients, 16 professionals, and 17 administrators from Ribeirão Preto, Sao Paulo, using an instrument adapted to evaluate TB. According to the informants, the coordination of healthcare provided to patients under the treatment of the Tuberculosis Control Program team was considered satisfactory; however, when there is a need to refer the patient to other care units there are weak points in the coordination of healthcare, which include: interruption of communication flow; and patients' incipient participation in the care process, with a need to increase the sense of responsibility for patient care and encourage patients to become active agents in the process.